DESIGN AND PROTOTYPING OF ELECTRIC CARRYING TRACTORS - Rizayana, Farid; Kwintarini, Widiyanti; Hermawan, Muhammad Reza; Bayuseno, Athanasius P; Jamari, Jamari (ROTOR, 2023)
Locations with hard-to-reach access make people living in 3T (Terluar/Front, Terpencil/Remote, Terbelakang/Backward) areas unable to enjoy quality fuel oil (BBM) at affordable prices. This research provides solutions for people in remote areas and communities in the 3T area to utilize agricultural equipment without dependence on fuel. The agricultural equipment in question is a Multifunctional Portable Tractor driven by an electric motor, using a battery. Batteries are recharged from solar sources through solar panels, water turbines and wind turbines. The research method used adopts the "Walter Franco" method (Franco et al., 2020). Product design and development involved 3 farmer groups from 3 different regions in West Java and six small machinery component industries in West Java, Indonesia. Research methodology involves the use of observations and field testing prototypes as instruments. This research resulted in innovative equipment that can be used for sloping land farming. This equipment is the only mechanical agricultural equipment that can be folded and carried by one person, so its contribution to research in inclined land farming is very large. This equipment is proven to cultivate land on sloping land profitably, so its contribution to farmers in Indonesia and other countries will be very significant Keywords: Carrying tractor, Electric drive, 3T, Sloping land, Agricultural mechanization